Development Of Volleyball Learning Media Through Video Animation In Palembang Junior High School - Koeswara, Dimas; Usra, Meirizal; Yusfi, Herri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aims to produce volleyball learning media products through animated videos at Junior Hight School 3 Palembang so that students are not bored in the learning process. This research uses research and development method. The subjects in this study amounted to 90 large-scale trial students and 30 small-scale trial students. The product produced in this study is a learning application, namely “Video animation of volleyball learning”. The results of this study regarding the feasibility of products assessed by material experts received a percentage score of 87% at stage 1 validation and 94% at stage 2 with a feasible category. Then validation by media experts obtained a percentage score of 93% at stage 1 validation and 95% at stage 2 with a decent category.  At the small-scale trial stage the product received an assessment of 87.6% categorized as “Feasible” and at the small-scale trial stage the product received an assessment of 97.4% and categorized as “Feasible”. Based on the validation and trial of the product “Video animation of volleyball learning”. shows that it is feasible to use in learning and suitable for students. This animated video also helps teachers in delivering material easily and fun so that students are interested in participating in learning.